Walt Disney's the jungle book - Kipling, Rudyard 1865-1936 (New York Centum, 2018)
The animal friends of the boy raised by wolves escort him out of the jungle to keep him safe from the tiger who seeks to kill him
1
Keywords: Jungles -- Fiction